Pengaruh Kelengkapan Fasilitas Banquet Terhadap Penyelenggaraan Event di Hotel Crystal Lotus Yogyakarta The Effect of Completeness Banquet Facilities On Implementing Event in Hotel Crystal Lotus Yogyakarta - Risandi, Muhammad Dudha; Handayani, Lutfi; Arifin, Samsul; Erryawan, Ervin (EBBANK, 2024)
This thesis entitles "The influence of banquet equipment on organizing events in Hotel Crystal Lotus Yogyakarta. The aim is to find out the completeness of the existing facilities at the Banquet Hotel Crystal Lotus Yogyakarta Yogyakarta and to find out the effect of the completeness of the facilities on the event in Hotel Crystal Lotus Yogyakarta. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The data analysis used by the author is the Spradley model data analysis.The results obtained from this study, of the 8 indicators of the completeness of the facilities that the author has set, there are 6 responses that say they have an effect on the ongoing event, there are 6 responses that say they might affect the event for different reasons, and there are 4 responses that say no effect on the event taking place. The hotel must complete the lack of facilities in the Crystal Lotus Hotel meeting room, regulate the use of equipment, especially equipment used by banquets. Adding employees to the banquet section so that there is no shortage of banquet workers.